POTRET PENGUATAN PENDIDIKAN KARAKTER DAN TANTANGANNYA DALAM PEMBELAJARAN DI SMP KABUPATEN PEMALANG - Alam, Mustika Alam; Muntoha Nasuha; Tity Kusrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education serves as a fundamental pillar in shaping a generation that is not only academically competent but also morally grounded and socially responsible. However, its implementation at the junior high school level (SMP) still faces numerous challenges, including the limited integration of character values into classroom instruction, low parental involvement, and weak student awareness of moral values. This study aims to analyze the needs in strengthening character education in SMPs, particularly in Pemalang Regency, by examining teachers’ understanding, the implementation of the Pancasila Student Profile Project (P5), student awareness, and the relationship between character education and academic achievement. Employing a quantitative descriptive-evaluative approach, data were collected through Likert-scale questionnaires distributed to teachers, students, and parents across four public junior high schools. The findings reveal that while teachers’ understanding of character education is relatively high (67%), only 42% are able to integrate it effectively into classroom practice. The implementation of P5 remains suboptimal, and parental involvement is still low (38%). Furthermore, the study identifies a significant positive correlation between strengthened character education and improved student academic performance. These results underscore the need for comprehensive efforts, including teacher training, enhanced student engagement, and stronger school-family collaboration. The outcomes of this research are expected to inform strategic planning for a more contextual, applicable, and sustainable model of character education.